Oblicz;
1i1/2+ 3i3/4=
3i1/2-2i5/7=
6i3/8-7i1/6=
-2i7/30-1i5/12=
2i2/3*2i1/4=
1i1/3:6=
1i2/7*(-4i2/3)=
(-3i3/8):(-2i1/4)=
(1i3/4-11/20)*1i1/9=
(1i3/4+1/8):(-1i7/18)=
doprowadz podane liczby do tej samej postaci (dziesietnej lub zwylkej)i wykonaj dzialanie ;
0,5+4/5
-1,5-5/8
1i1/50:(-0,01)
0,4-1i3/10
0,25*7.10
7/8*0,5

3

Odpowiedzi

2010-02-07T11:34:46+01:00
1 ½ + 3 ¾ = 1 2/4 + 3 ¾ = 4 5/4 = 5 ¼
3 ½ - 2 5/7 = 3 7/14 - 2 10/14 = 3/14
6 ⅜ - 7 1/6 = 6 9/24 - 7 4/24 = -1 5/24
-2 7/30 - 1 5/12 = -2 14/60 - 1 25/60 = - 3 39/60
2 ⅔ * 2 ¼ = 8/3 * 9/4 = 72/12 = 6
1 ⅓ : 6 = 4/3 * 1/6 = 4/18 = 2/9
1 2/7 * (-4 ⅔) = 9/7 * (- 14/3) = - 126/21 = -6
(-3 ⅜) : (-2 ¼) = (-27/8) : (-9/4) = (-27/8) * (-4/9) = 108/72 = 1 36/72 ½
(1 ¾ - 11/20) * 1 1/9 = (1 15/20 - 11/20) * 1 1/9 = 1 4/20 * 1 1/9 = 1 ⅕ * 1 1/9 = 6/5 * 10/9 = 60 / 40 = 6/4 = 1 2/4 = 1½
(1 ¾ + ⅛) : (- 1 7/18) = (1 6/8 + ⅛) * (-25/18) = (1 ⅞) * (-25/18) = 15/8 * (-25/18) = (-375/144) = -2 87/144

0,5 + ⅘ = ½+⅘= 5/10 + 8/10 = 13/10 = 1 3/10 = 1,3
-1,5 + ⅝ = - 1½ + ⅝ = -1 4/8 + ⅝ = -⅞
1 1/50 : (-0,01) = 51/50 / (-1/100) = 51/50 * (-100/1) = (-5100/50) = (-510/5) = -102
0,4 - 1 3/10 = 0,4 - 1,3 = 0,9
0,25*7/10 = 0,25 * 0,7 = 0,175
⅞ * 0,5 = ⅞ * ½ = 7/16
1 1 1
2010-02-07T11:38:33+01:00
1i1/2+ 3i3/4= 5 1/4
3i1/2-2i5/7= 11/14
6i3/8-7i1/6= -0,8
-2i7/30-1i5/12= - 49/60
2i2/3*2i1/4= 6
1i1/3:6= 4,5
1i2/7*(-4i2/3)= -6
(-3i3/8):(-2i1/4)= 2/3
(1i3/4-11/20)*1i1/9= 1i 1/3
(1i3/4+1/8):(-1i7/18)= -1i 1/7

0,5+4/5= 1/2 + 4/5 = 1 i 3/10
-1,5-5/8= -1 i 1/2 - 5/8= 7/8
1i1/50:(-0,01)= 1,2 :(-0,01)= -120
0,4-1i3/10= 0,4- 1,3= 0,9
0,25*7.10= 1,775
7/8*0,5= 7/8* 1/2= 7/16
2010-02-07T11:48:49+01:00
1i1/2+ 3i3/4= 3/2+15/4= 6/4+15/4= 21/4= 5 1/4
3i1/2-2i5/7= 7/2-19/7= 49/14-38/14= 11/14
6i3/8-7i1/6=51/8-43/6= 153/24-172/24= -19/24
-2i7/30-1i5/12= 67/30-60/12= 134/60-300/60= 166/60= 2 46/60= 2i 23/30
2i2/3*2i1/4= 8/3*9/4= 2/1*3/1= 2*3= 6
1i1/3:6= 4/3:6/1= 4/3*1/6= 2/3*1/3= 2/9
1i2/7*(-4i2/3)= 9/7* (-14/3)= 3/1*(-2/1)= -6
(-3i3/8):(-2i1/4)= (-27/8):(-9/4)= (-27/8)*(-4/9)= (-3/2)*(-1/1)= 3/2= 1i 1/2
(1i3/4-11/20)*1i1/9= (7/4-11/20)*10/9= (35/20-11/20)*10/9= 24/20*10/9= 24/2*1/9= 24/9= 2i 6/9= 2i 2/3
(1i3/4+1/8):(-1i7/18)= (5/4+1/8):(-25/18)= (10/8+1/8):(-25/18)= 11/8:(-25/18)= 11/8*(-18/25)= 11/4*(-9/25)= 99/100

0,5+4/5= 0,5+0,8= 1,3
-1,5-5/8=(-1i1/2-5/8= 3/2-5/8= 12/8-5/8= 7/8
1i1/50:(-0,01)= 1.02:(-0,01)= -102
0,4-1i3/10= 0.4-1.3= -0,9
0,25*7.10=0.25*0,7= 0,175
7/8*0,5=7/8*1/2= 7/16